AI, Sacred Violence, and War$1 (BThe Case of Gazas - Gray, Chris Hables; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
This open access book is about how Israel is using Algorithmic Intelligence (AI) and other computer technology in military operations in the Gaza Strip to achieve goals based on ancient religious entitlements. Changes in Israel Defense Force (IDF) ethical codes and innovation policies have not led to victory, but have resulted in a wide range of War Crimes and Crimes Against Humanity in a strategy focused on The Torture of Gaza, which includes ethnic cleansing and is approaching genocide. It covers the history of using AI in war, and current U.S. and Israeli military AI technologies such as Maven, Iron Dome, Pegasus, the Alchemist, Gospel, Lavender, and Where$1 (Bs Daddy, all tested and perfected in the Palestinian Laboratory and marketed as such. This book also places the current data-driven and AI-directed assault on Palestine in the context of Postmodern War, which precludes military victories and enshrines the profits and power of the U.S.-Israeli military-industrial complex in a system of perpetual war and militarized technological innovation. Through an analysis of Israeli military policies, AI, sacred texts, and the basic tenets of postmodern war, the book ultimately reveals the limits of the IDF$1 (Bs embrace of illusions about new technologies producing actual victory. War today is about winning hearts and minds, not body counts. As fundamentalist politics achieve more and more power around the world in the context of new information technologies, there is growing danger to the future of all of us. Chris Hables Gray studies the social and political implications of technoscience. Author of 102 peer-reviewed articles and book chapters and Postmodern War (1997), Cyborg Citizen (2001), Peace War and Computers (2005) and Virus is a Language: AI, QAnon, COVID-19 and the New Abnormal (2025). Lead editor of The Cyborg Handbook (1995) and Modified: Living as a Cyborg (2021). He teaches at the University of California at Santa Cruz, gardens and longs for a cat.s
Chapter 1: An Introduction to AI in a Biblical War -- Chapter 2: Relentless History -- Chapter 3: Israeli Military Policies -- Chapter 4: AI at War -- Chapter 5: End Times.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Security, International; Middle East -- Politics and government; Politics and war; International Security Studies; Middle Eastern Politics; Military and Defence Studies